(untitled) (Fiep Bulletin - online, 2014)
The present work had as goal redeem the jokes and the traditional games used by the children in her daily. The analyzed depositions allow to verify that in general, the children know and cite several games, without, however to there be variation of the same. It can say that they repeat the most well-known and used games.The acquis of games of children interviewed seems limited